Toward Reduction in Antibiotic Use for Pediatric Otitis Media: Predicting Parental Compliance with "Watchful Waiting" Advice. Issue 11 (2nd November 2017) - MacGeorge, Erina L.; Smith, Rachel A.; Caldes, Emily P.; Hackman, Nicole M.
Abstract : "Watchful waiting" (WW) can reduce unnecessary antibiotic use in the treatment of pediatric otitis media (ear infection), but the utility of the strategy is impaired by underutilization and noncompliance. Guided by advice response theory (ART), the current study examines how parental compliance with WW and trust in the prescribing physician is predicted by evaluative and affective responses to the advice. Parents ( N  = 134) of at least one child aged 5 years or younger completed questionnaires that assessed responses to WW advice they received for their youngest child. Perceptions of the advantage from and capacity to undertake WW, the child's level of pain, and the tact (autonomy-granting politeness) of the health care provider predicted compliance and provider trust both directly and indirectly, through advice quality and negative affect. The study suggests modifications to ART that will extend its scope and provides practical guidance for health care providers seeking to improve parent compliance with WW advice.